Tatbiq Kitab Al-Qolam fi Ta’lim Kitabah Pegon Al-Arabiyah fi Al-Maahid Al-Islamiyah Madura - Rofi'i, M. (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The existence of Pegon letters in various pesantren institutions is needed for the translation of Arabic books into Javanese or Indonesian. This is done to make it easier to read Arabic or translate Arabic. One of the educational institutions that still maintains Pegon writing in its education is Syaichona Moh. Cholil Bangkalan Islamic Boarding School because new students (Santri) have different educational backgrounds. They know Pegon script from their respective homes and those who do not know Pegon script because at home they do not study at Madrasah Diniyah. Al-Qolam is a book written by Ust. Mohammed Tuba. The book is one of the books that is the basis for learning in the basic class (Shifir) at Syaichona Moh. Cholil Bangkalan Islamic Boarding School. The book has been classified to make it easier for new Santri who do not know Pegon writing and Arabic writing in learning. To find this, researchers used qualitative research methods. The targets of this research are teachers and students of the elementary class (Shifir) at the Syaichona Moh. Cholil Islamic Boarding School in Bangkalan. Then to collect data with observation, interview and documentation methods and researchers use data reduction, data presentation and conclusion drawing. The results of this study include how to use Al-Qolam books in learning to write, so that Arabic is a learning process: the teacher instructs students to memorize the alphabet and Pegon letters, then the teacher teaches the material on the blackboard and students write what the teacher writes. And in the educational process the teacher must multiply the application of the material.